Human body - Dorling Kindersley Publishing, Inc (New York : Dorling Kindersley, 2001)
Human Body is a concise guide to the structure, functions, and disorders of the body. Using full-color, highly detailed illustrations and clear, accessible language, this book is a fascinating introduction to how the body works and what may go wrong. The first part, Anatomy of the Human Body, begins with a medical atlas that shows how the parts of the body fit together. Each individual body system - such as the skeletal and digestive systems - is then fully illustrated and explained in detail. A compelling section on the human life cycle examines the changes in the body from conception to old age. In the second part of the book, Diseases and Disorders, some of the most common disorders are described and illustrated, system by system, with explanations of exactly what goes wrong and why. Medical conditions covered include infections, injuries, and cancer. Finally, there is a concise glossary of medical terms
Anatomy of the human body -- Diseases and disorders
Includes index
Keywords: Human anatomy -- Atlases; Human body -- Atlases; Pathology -- Atlases; Anatomy -- Atlases; Pathology -- Atlases; Atlases